Clinical management of delirium: The response depends on the subtypes. An observational cohort study in 602 patients. Issue 1 (February 2020) - Zipser, Carl Moritz; Knoepfel, Silvana; Hayoz, Peter; Schubert, Maria; Ernst, Jutta; von Känel, Roland; Boettger, Soenke
Abstract: Objective: The hypoactive, hyperactive, and mixed subtypes of delirium differently impact patient management and prognosis, yet the evidence remains sparse. Therefore, we examined the outcome of varying management strategies in the subtypes of delirium. Methods: In this observational cohort study, 602 patients were managed for delirium over 20 days with the following strategies: supportive care alone or in combination with psychotropics, single, dual, or triple+ psychotropic regimens. Cox regression models were calculated for time to remission and benefit rates (BRs) of management strategies. Results: Generally, the mixed subtype of delirium caused more severe and persistent delirium, and the hypoactive subtype was more persistent than the hyperactive subtype. The subtypes of delirium were similarly predictive for mortality ( P = 0.697) and transfer to inpatient psychiatric care ( P = 0.320). In the mixed subtype, overall, psychotropic drugs were administered more often ( P = 0.016), and particularly triple+ regimens were administered more commonly compared to hypoactive delirium ( P = 0.007). Patients on supportive care benefited most, whereas those on triple+ regimens did worst in terms of remission in all groups of hypoactive, hyperactive, and mixed subtypes (BR: 4.59, CI 2.01–10.48; BR: 4.59, CI 1.76–31.66; BR: 3.36, CI 1.73–6.52; all P < 0.05). Significance of results: The mixed subtype was more persistent to management than the hypoactive and hyperactive subtypes. Delirium management remains controversial and, generally, supportive care benefited patients most. Psychopharmacological management for delirium requires careful choosing of and limiting the number of psychotropics.